Pozycja prawna pracowników kolejowych w okresie militaryzacji PKP w drugiej połowie lat czterdziestych XX wieku - Ogurek, Artur (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The article is an attempt to present the changes in legal status of railway workers as a result of the militarization of railways in Poland in the second half of the 1940s, including the context and consequences of the militarization process. Literature research as well as query and analysis of legal acts led us to the conclusion that as a result of recognizing PKP employees as called up for military service, their subordination for committed crimes, the jurisdiction of the Military Prosecutor’s Office of the Polish State Railways, and the Military Court of PKP were established. In the article I also describe the main factors of the transformation the special justice system underwent in the analyzed period, proving that it was not the first militarization of the railways in Poland, as well as that the legal acts introducing the militarization in 1944 referred to — at least partially — the tradition of the previous double militarization of railways in the Second Polish Republic.
Keywords: demilitaryzacja; militaryzacja; Polskie Koleje Państwowe (PKP); Wojskowa Prokuratura PKP; Wojskowy Sąd PKP